OpenStack cloud application development - Adkins, Scott; Belamaric, John; Giersch, Vincent; Makogon, Denys; Robinson, Jason E. (Wrox, a Wiley brand, 2016)
Leverage the power of OpenStack to develop scalable applications with no vendor lock-in OpenStack Cloud Application Development is a fast-paced, professional book for OpenStack developers, delivering comprehensive guidance without wasting time on development fundamentals